The fight against hate crimes - McKay, C. R. (writer of juvenile literature) (Topics today, 2022)
"Despite efforts to curtail them, hate crimes are still occurring around the world. Each day, many people are becoming victims of hate crimes because of the way they look, what the believe in, or who they love. With the help of full-color photographs, discussion questions, and annotated quotes, readers examine the history of hate crimes and discover the heroes who are fighting against hate today. The informational text highlights recent events that have led to outcries against hate crimes around the world, and explores ways that societies can help mitigate differences between others and work together to eradicate hate crimes"--